The mystic leeway - Gregg, Frances, 1884-1941.; Jones, Ben, 1930- ([Ottawa, Ont.] : Carleton University Press, 1995)
Who is Frances Gregg? In her youth she was a poet in her own right, a friend of Ezra Pound, and an intimate of Hilda Doolittle and John Cowper Powys. In our literary history, particularly the history of Modernism, she has been a mysterious presence. Now, with this publication for the first time of The Mystic Leeway, we have Gregg's testament to her lovers, her life, her deeply troubled times, and to Art. Written over the three years before her tragic death in the bombing of Plymouth in 1941, this memoir.
Cover13; -- Contents -- List of Illustrations -- Editor's Preface -- Editor's Introduction -- "My Hilda" -- Frances Gregg: First Hand -- Note on the Text -- The Mystic Leeway -- Endnotes -- Works Cited.
Includes bibliographical references.
Print version record.
English.
eBooks on EBSCOhost
Keywords: Gregg, Frances, -- 1885-1941.; H. D. -- 1886-1961 -- Friends and associates; Gregg, Frances, -- 1885-1941.; H. D. -- 1886-1961 -- Amis et relations; Gregg, Frances, -- 1885-1941; H. D. -- 1886-1961; Gregg, Frances; POETRY -- American -- General; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh; Friendship; Autobiografie; Electronic book